A survey of small bowel modelling and its applications for capsule endoscopy. (May 2022) - Liu, Yang; Tian, Jiyuan; Manfredi, Luigi; Terry, Benjamin S.; Prasad, Shyam; Rahman, Imdadur; Marlicz, Wojciech; Koulaouzidis, Anastasios
Abstract: The small intestine, an anatomical site previously considered inaccessible to clinicians due to its small diameter and length, is the part of the gastrointestinal tract between the stomach and the colon. Since its introduction into clinical practice two decades ago, capsule endoscopy has become established as the primary modality for examining the surface lining of the small intestine. Today, researchers continue to develop ground-breaking technologies for novel miniature devices aiming for tissue biopsy, drug delivery and therapy. The purpose of this paper is to provide researchers and engineers in this area a comprehensive review of the progress in understanding the anatomy and physiology of the small intestine and how this understanding was translated to virtual and physical test platforms for assessing the performance of these intestinal devices. This review will cover both theoretical and practical studies on intestinal motor activities and the work on mathematical modelling and experimental investigation of capsule endoscope in the small intestine. In the end, the requirements for improving the current work are drawn, and the expectations on future research in this field are provided. Highlights: This survey covers the studies on small-bowel motor activities. It studies the modelling of the capsule endoscope in the small intestine. The modelling works include analytical and finite element methods. Experimental investigation of the small intestine is fully reviewed. It is suitable for robotic engineers who are developing intestinal devices.